Pelatihan Pembuatan Soal Menggunakan Google Formulir Di SDN Batangkaluku - Wiwik Wiji Astuti (ADPERTISI, 2022)
This community service is carried out with the aim of increasing the knowledge and skills of teachers in utilizing the Google Forms application in question-making activities. This community service was carried out in November 2020. The implementation of this community service was carried out using the presentation, training, and evaluation methods. The conclusions obtained through this community service activity are; 1) improve the knowledge and understanding of teachers at SDN Batangkaluku about the Google Forms application, 2) improve the ability of teachers at SDN Batangkaluku in making questions using the Google Forms application. Keywords: Training, Questions, Google Forms